An Analysis of Stakeholder Management in Project Performance: A Case of Lusaka 400 Road Construction Projects - Dalisani Phiri; Kelvin Chimbomba (Journal of Arts, Humanities and Social Science)
Roads are vital to the development agenda of any country. Road infrastructure is a necessary and significant component in the development process. However, numerous studies have reported high failure rates in managing cost overruns and project delays during the implementation of the Lusaka 400. Stakeholder management is widely recognized as crucial for project success. This study provided a detailed examination of stakeholder management practices and their impact on road project performance. The study utilized a mixed research method. Purposive sampling was used to determine the target population. Descriptive analysis was used to calculate measures of association to quantify the strength and direction of relationships between variables. This study used triangulation to interpret themes and patterns from the collected qualitative data. The findings of the study revealed that stakeholder management strategies significantly impact the overall success of construction projects like the Lusaka 400 road project. The findings of the study revealed that stakeholder management strategies significantly impact the overall success of construction projects like the Lusaka 400 road project. Effective strategies, particularly those emphasizing communication and regular engagement were positively correlated with better project outcomes. However, the study also identified areas for improvement, such as the need for more frequent updates and joint supervision visits, which could further enhance the effectiveness of these strategies. The study concluded that effective stakeholder management practices should be consistently applied and adapted to evolving project needs to ensure sustained success.